Freight transport impacts from the economic crisis in Greece. (July 2017) - Moschovou, Tatiana P.
Abstract: During the last eight years, Europe, and the world as general, has been experiencing a situation of sudden economic recession resulted in economic and financial crisis. According to the IMF (2009), this is the worst recession of the last decades since economies, countries and global GDP have been seriously affected. A sector of the economy that has significantly been impaired is road freight transport. The scope of this paper is to investigate the effect of this crisis on road freight transport in Greece. The analysis starts by examining global and European data and trends while presenting comparable Greek economic and freight transport data for a series of years starting in 2003. This analysis and mapping of data shows some plausible correlations between economic and freight transport indicators and identified visible patterns. The paper examines the possibility of constructing mathematical relations between tonnes or t-km of road freight and GDP for Greece, which were the only relations showing a statistically significant correlation. The overall conclusion is that the impacts on freight transport are visible but quite pronounced as freight transport volumes and output have been substantially unstable or reduced over these years and this trend is visible when mapping the relevant data as well as in more detailed statistical analysis. Highlights: Economic growth and road freight performance, measured in t-km, are key elements of road freight intensity. Investigation of the effect of economic and financial crisis on road freight transport in Greece. Analysis and mapping of economic and road freight transport data for a series of years starting from 2003 for Greece. Formulation of mathematical relations between tonne or t-km of road freight and GDP for Greece.